Temporary agency employment in Germany: A strategic "buffer" for firms and regions in the crisis? - Uwe Neumann (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
In many European countries the number of employees hired via temporary work agencies has increased considerably over the past two decades, up to around 2% of the total workforce in the European Union today. Different studies have found the demand for agency employment to precede GDP growth. This paper explores to what extent firms utilised agency work as a strategic 'buffer' to adapt to variation in labour demand in Germany over the period 2006-2014, i.e. before, during and after the crisis of 2008/2009. Drawing on microdata from a representative employer survey (IAB Establishment Panel) and statistics on regional labour markets, the analysis finds only limited evidence on a systematic firm-level buffer function of temporary agency work. Rather, in many firms hiring from agencies is possibly part of a business strategy relying on flexible recruitment. An analysis of the average treatment effect on the treated (ATT) using a propensity score matching procedure suggests that particularly in regions with high unemployment, such flexibility during the crisis supported adaptation of client firms to economic change, since they were less reluctant than non-clients to hire after the crisis. – – In zahlreichen europäischen Staaten hat die Zeitarbeit in den vergangenen beiden Jahrzehnten deutlich an Bedeutung gewonnen. Heute sind etwa 2% der Arbeitnehmer in der Europäischen Union bei Zeitarbeitsfirmen beschäftigt. Verschiedene Studien haben festgestellt, dass der Beschäftigungsumfang im Zeitarbeitssektor dem Wirtschaftswachstum vorausläuft. Dieser Beitrag untersucht, ob und inwieweit entleihende Unternehmen in Deutschland die Zeitarbeit als strategischen 'Puffer' zur Anpassung an die bei ihnen fluktuierende Arbeitsnachfrage im Zeitraum 2006-2014, d.h. vor, während und nach der Krise von 2008/2009, nutzten. Unter Zugriff auf Mikrodaten des IAB-Betriebspanels und regionale Arbeitsmarktstatistiken findet die Analyse nur sehr begrenzte Belege für eine systematische 'Puffer'-Funktion der Zeitarbeit. Oftmals nutzen Entleihfirmen die Zeitarbeit vielmehr als Mittel zur Flexibilisierung ihres Personalmanagements. Eine Analyse der Treatmenteffekte (Average Treatment Effect on the Treated, ATT) hinsichtlich der Job- und Lohnentwicklung in Entleihfirmen mit Hilfe eines Propensity Score Matching-Verfahrens führt zu dem Ergebnis, dass diese Art der Flexibilisierung in Regionen mit hoher Arbeitslosigkeit dort ansässige Entleihfirmen offenbar nach der Krise insgesamt zu mehr Einstellungen bewegt hat als vergleichbare Firmen, die während der Krise keine Zeitarbeitskräfte beschäftigten.
Keywords: L25; J23; M54; R11; 330; Temporary agency work; regional labour markets; establishment data; propensity score matching